Toponimi Bangunan Bersejarah di Kampung Kauman Yogyakarta - Aris Romadhon (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
This research examines the toponymy of historical buildings in Kauman village, Yogyakarta. Language has a role as a form of symbolism to reveal the origin and culture of place naming, one of which is found in the naming of a building. As one of the villages in Yogyakarta City that represents this, this study will reveal the linguistic features of naming, the toponymic aspects of naming, then look for the origin of the naming of historical buildings in Kauman village to find out how the community views based on the name of historical buildings in Kauman Yogyakarta. Data were collected through observation, literature study, and interviews (record and note) which were then analyzed based on aspects of naming historical buildings in Kauman village. The result found is that the naming of historical buildings in Kauman Village is influenced by foreign and local cultures and languages. The influence of Arabic, Dutch, and the use of the names of Arab figures in the naming of buildings was found. In addition, the use of the Javanese language was found in the naming. The formation process is affixation, abbreviation abbreviation, and there is naming with van ophuijsen spelling. The findings of the toponymy aspects of historical buildings in Kauman village Yogyakarta were found based on: (1) manifestation aspect, which is based on the appearance of the earth, (2) social aspect, which is based on the name of a figure, based on profession, and based on community interaction, and (3) cultural aspect based on cultural elements. Through this study, it is known that the naming of buildings is not only a form of symbolism, but it can be seen that the perspective of the Kauman village community is influenced by javanese and arabic culture.